Pengaruh Media Pembelajaran Roda Putar Terhadap Motivasi Belajar Matematika Siswa Kelas III SD Negeri 224 Palembang - Desi Puspita Sari; Misdalina Misdalina; Tanzimah Tanzimah (Journal on Education, 2024)
This study aims to determine the influence of rotary wheel learning media on the motivation to learn mathematics of grade III students of SD Negeri 224 Palembang. The research method used is quantitative type of experiment with the form of true experimental design and posttest-only control design research design. The population in this study amounted to 130 students, who were sampled in this study class III.D as a control class and class III.E as an experimental class. The sample in this study used a simple random sampling technique. The data collection techniques used are questionnaires (questionnaires) and documentation. The data analysis technique used is the t test (independent sample t test). From the results of research data processing with the help of the SPSS application, a sig value (2-tailed) = 0.000 < 0.05 and a thit value = 4.724 > ttable = 1.677. In accordance with the prerequisites of the hypothesis test, it is rejected and accepted. This shows that there is H_0 H_aan influence of rotary wheel learning media on the motivation to learn mathematics of grade III students of SD Negeri 224 Palembang.